2017
DOI: 10.1080/19475705.2017.1413012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria risk evaluation by integrating an analytical network process approach into GIS-based sensitivity and uncertainty analyses

Abstract: Geographic information system (GIS)-based multi-criteria decision analysis (MCDA) is commonly used to solve a range of complex spatial problems. We have incorporated an analytical network process (ANP) as a central part of MCDA and used this approach for land subsidence susceptibility mapping (LSSM). We used an ANP approach in combination with the concepts of global sensitivity and uncertainty analyses, in order to minimize any associated errors. This approach was tested for a LSSM application in northwestern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 56 publications
0
68
0
Order By: Relevance
“…In order to deal with these issues, many studies have aimed at reducing the amount of inherent uncertainty associated with the AHP method. There are some studies that have suggested the use of sensitivity and uncertainty analyses and integration of the AHP with statistical approaches such as the Monte Carlo simulation [38,39]. The fuzzy-AHP is based on different membership functions that are considered to be an effective and flexible technique in some cases [40].…”
Section: Literature Review On Mcdm For Transportation and Consultatiomentioning
confidence: 99%
“…In order to deal with these issues, many studies have aimed at reducing the amount of inherent uncertainty associated with the AHP method. There are some studies that have suggested the use of sensitivity and uncertainty analyses and integration of the AHP with statistical approaches such as the Monte Carlo simulation [38,39]. The fuzzy-AHP is based on different membership functions that are considered to be an effective and flexible technique in some cases [40].…”
Section: Literature Review On Mcdm For Transportation and Consultatiomentioning
confidence: 99%
“…The authenticity of spatial simulation models and GIS‐MCDA techniques depend on how the relative importance of each criteria has been calculated (Ghorbanzadeh, Feizizadeh, & Blaschke, ). The personal preferences of decision maker in determining the criteria weights directly affect the accuracy of model because the decision maker's individual preferences are assumed to be actual rules in the decision‐making process (Ghorbanzadeh et al, ). AHP and DEA methods are commonly used in the literature for choosing the best alternative and to determine the weights of alternatives and criteria.…”
Section: Introductionmentioning
confidence: 99%
“…From a geological point of view, the study area coincides with the same lithological formation, namely a high level piedmont fan and valley terrace deposits Q ft1 belonging to the Quaternary age (Khaleghi and Shahverdizadeh 2014). The primary local activity is agriculture, including irrigated and rain fed agriculture and orchards (Khorrami 2016;Ghorbanzadeh et al 2017). Agriculture in the region requires a huge amount of surface and underground water.…”
Section: Study Areamentioning
confidence: 99%
“…Lee et al (2012) assessed ground subsidence susceptibility (GSS) in South Korea using artificial neural networks (ANN). A GIS-MCDA method was also used by Ghorbanzadeh et al (2017) to identify areas that are prone to land subsidence in the Marand plain, while Dehghan-Soraki et al (2015) applied ASAR and PALSAR data to analyze and measure the land surface change rates caused by subsidence. Karimzadeh et al (2013) and Karimzadeh (2015) used the same type of data in order to distinguish the surface deformation in another basin in the Northwest of Iran.…”
Section: Introductionmentioning
confidence: 99%